2011
DOI: 10.1111/j.1756-185x.2011.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of anti‐streptolysin O antibodies: their role in evaluating rheumatic diseases

Abstract: Elevated ASO titers can be found in various clinical conditions other than the typical post-streptococcal associated diseases. In these cases it is not necessarily accompanied by positive culture and does not correlate with inflammatory parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
13
0
2
Order By: Relevance
“…The results were similar to the study by Ben-Chetritand alon a population of 28 subjects 13.8% of those under 18 had a history of angina, pharyngitis or even tonsillectomy and had a significant positive ASLO in hospitalized patients (33%) with highertiter rate compared to healthy controls (8%) [12]. According to the literature, 20% of group A streptococci do not produce streptolysin O.…”
Section: Discussionsupporting
confidence: 88%
“…The results were similar to the study by Ben-Chetritand alon a population of 28 subjects 13.8% of those under 18 had a history of angina, pharyngitis or even tonsillectomy and had a significant positive ASLO in hospitalized patients (33%) with highertiter rate compared to healthy controls (8%) [12]. According to the literature, 20% of group A streptococci do not produce streptolysin O.…”
Section: Discussionsupporting
confidence: 88%
“…It should also be considered that etanercept is also affecting other body organs: For example, clinical studies in rheumatoid arthritis have indicated that etanercept -prescribed because of its anti-inflammatory activity-, can increase the risk of developing inflammatory bowel disease, lung infections, and pancytopenia ( Thavaranjah et al, 2009 ; Santana et al, 2012 ; O’Toole et al, 2016 ), but these side effects of etanercept are not frequently reported and the medication is generally well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…In a significant number of cases, the initial infection is subclinical 5. Throat cultures taken at the time of presentation with rheumatic fever or nephritis may be negative because of clearance of GAS by the host immune system during the latent period5 or due to previous antibiotic treatment 6. Interpretation of throat cultures at the time of presentation with a possible poststreptococcal complication is further confounded because a swab positive for GAS may represent asymptomatic carriage and not infection.…”
Section: Introductionmentioning
confidence: 99%